2013
DOI: 10.1103/physrevc.88.015208
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy reactionsKpΣ0π0,Λπ0

Abstract: Low energy reactions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 124 publications
3
16
0
Order By: Relevance
“…Obvious roles of the low-lying negative parity states, Λ(1405), Λ(1520) and Λ(1670), are found in the K − p → Σ 0 π 0 , K0 n reactions, where we have extracted their strong coupling properties. For example, we found that Λ(1670) should have a very weak coupling to KN, while Λ(1520) needs a strong coupling to KN, which can not be well explained with the symmetry constituent quark model in the S U(6) ⊗ O(3) limit [54].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Obvious roles of the low-lying negative parity states, Λ(1405), Λ(1520) and Λ(1670), are found in the K − p → Σ 0 π 0 , K0 n reactions, where we have extracted their strong coupling properties. For example, we found that Λ(1670) should have a very weak coupling to KN, while Λ(1520) needs a strong coupling to KN, which can not be well explained with the symmetry constituent quark model in the S U(6) ⊗ O(3) limit [54].…”
Section: Introductionmentioning
confidence: 76%
“…This model has been well developed and widely applied to meson photoproduction reactions [56][57][58][59][60][61][62][63][64]. Its recent extension to describe the πN [65] and KN [40,54] reactions also turns out to be successful and inspiring.…”
Section: Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recently, we systematically studied the reactions K − p → Σ 0 π 0 , Λπ 0 ,K 0 n in a chiral quark model. 2 We found that Λ(1670) should have a very weak coupling toKN , while Λ(1520) needs a strong coupling toKN , which cannot be well explained with the symmetry constituent quark model in the SU(6)⊗O(3) limit. 2 To obtain more strong coupling properties and better understandings of these low-lying Λ states, we continue study another important reaction K − p → Λη.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, we systematically studied the reactions K − p → Σ 0 π 0 , Λπ 0 ,K 0 n in a chiral quark model approach. 6,7 Good descriptions of the experimental observations are obtained. The roles of the low-lying Λ and Σ hyperon resonances in these processes are carefully analyzed.…”
Section: Introductionmentioning
confidence: 99%